Analisis Pengaruh Kemampuan dan Motivasi Terhadap Kinerja Koordinator Statistik Kecamatan (KSK) Di BPS Provinsi Maluku - Sapulette, Ludy (Arthavidya Jurnal Ilmiah Ekonomi, 2013)
The research was conducted to 1) determine the level of influence on the performance capability of Statistics District Coordinator (SWC) in BPS Maluku province, 2) determine the influence of motivation on the performance of Statistics District Coordinator (SWC) in BPS Maluku province, and 3) determine the level of influence variable simultaneous ability and motivation on the performance of Statistics District Coordinator (SWC) in BPS Maluku province. This study was conducted on six (6) districts / municipalities in the province of Maluku Maluku Tenggara, Tual Town, Central Maluku, West Ceram Regency, West Southeast Maluku and Ambon Town, the 42 (forty-two) districts, and implemented March-May 2011. The variables in this study consisted of the independent variable is the ability and motivation, while the dependent variable is the performance. The population in this study are all Statistics District Coordinator (SWC) contained in the 6 districts / cities in BPS Maluku province, amounting to 42 people, as well as a sample in this study. The methods used to analyze the data is descriptive analysis and Multiple Linear Regression. The results showed that the partial variables consisting of indicators of the ability of the knowledge and skills have a positive and significant impact on the performance of the SWC in BPS Maluku province. There is a positive and significant relationship between motivational variables consisting of indicators of need for achievement, need for affiliation and need for power with a partial performance. Simultaneously ability and motivation variables have positive and significant impact on performance. The contribution of the independent variable on the dependent variable explained by the determinant coefficient (R2) of 69.0% and the rest is influenced by other variables outside the model. While the magnitude of the correlation coefficient (R) of 83.10%, which means there is a strong relationship between ability and motivation on performance.Keywords: ability, motivation, performance